Hyperglycemia and Cerebral Blood Flow in Drowning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Serial blood glucose levels and cerebral blood flow within 48 hours of admission were correlated with the clinical courses of 20 children with severe near-drowning in the Division of Child Neurology, the Department of Pediatrics, and Section of Neuroradiology, Loma Linda University School of Medicine, Loma Linda, CA.